Acetaminophen‐induced hepatocyte injury: C2‐ceramide and oltipraz intervention, hepatocyte nuclear factor 1 and glutathione S‐transferase A1 changes. Issue 12 (6th August 2019) - Chang, Yicong; Wang, Feng; Yang, Yang; Zhang, Yuanyuan; Muhammad, Ishfaq; Li, Rui; Li, Changwen; Li, Ying; Shi, Chenxi; Ma, Xin; Hao, Beili; Liu, Fangping
Abstract: Acetaminophen (APAP) is an antipyretic and analgesic, which is commonly associated with drug‐induced hepatic injury. C2‐ceramide plays a key role in mediating cell life activities, and oltipraz was extensively studied as a cancer chemopreventive agent. Glutathione S ‐transferase A1 (GSTA1) acts as a vital liver detoxification enzyme. Hepatocyte nuclear factor 1 (HNF‐1) regulates various cellular signaling pathways. In this study, we investigated the effects of C2‐ceramide and oltipraz on APAP‐induced hepatocyte injury and the changes of HNF‐1 and GSTA1. Results showed that C2‐ceramide (6 μmol/L) exacerbated APAP‐induced hepatocyte injury and caused a significant decrease ( P < .01) in HNF‐1 and GSTA1 expressions. Meanwhile, GSTA1 content in supernatant was significantly increased ( P < .01). In contrast, oltipraz (8 μmol/L) reduced the injury and significantly elevated ( P < .01) HNF‐1 and GSTA1 expressions while GSTA1 content in supernatant was significantly decreased ( P < .01). In conclusion, these findings revealed that C2‐ceramide inhibited HNF‐1 and GSTA1 expression and exacerbated hepatocyte injury, while oltipraz treatment results in the reduction of hepatocyte injury, and promoted HNF‐1 and GSTA1 expression. Additionally, the changes in HNF‐1 and GSTA1 were related to APAP‐induced hepatocyte injury. These results were useful to investigate the mechanism of an antipyretic and analgesic drug combination. Abstract : Acetaminophen (APAP) is an antipyretic and analgesic, and is commonly associated with drug‐induced hepatic injury. C2‐ceramide plays a key role in mediating cell life activities, and oltipraz was extensively studied as a cancer chemopreventive agent. Results revealed C2‐ceramide (6 μmol/L) exacerbated hepatocyte injury and oltipraz (8 μmol/L) results in the reduction of hepatocyte damage. In hepatocyte injury induced by APAP, C2‐ceramide could inhibit hepatocyte nuclear factor (HNF)‐1 and glutathione S ‐transferase A1 (GSTA1) expression, while oltipraz could promote HNF‐1 and GSTA1 expression.